Impaired Liver Function in the Use of Clozapine as an Antipsychotic - Aziz, Abdul; Herawati, Fauna; Pratama, Jainuri Erik; Gondokesumo, Marisca Evalina (Journal of Food and Pharmaceutical Sciences, 2025)
Clozapine is an atypical antipsychotic used to treat psychosis, mainly as a second choice for patients with refractory schizophrenia and recommended to manage schizophrenia that does not respond to other therapies. Clozapine is also often associated with elevated transaminase levels without clinical symptoms. In this case, a 45-year-old man, who had been diagnosed with schizophrenia since October 2020, was undergoing treatment with various antipsychotic drugs, including clozapine. About a week before hospitalization, there was a change in the patient's behavior. Due to this condition, the patient was brought to the outpatient psychiatric clinic at Airlangga University Hospital Surabaya, the patient was given clozapine 25 mg therapy at night, but the symptoms experienced were getting worse. The patient was finally taken for hospitalization at Dr. Soetomo Hospital Surabaya. While undergoing treatment at the hospital, the patient was given clozapine 10 mg therapy in the morning and at night, in addition, Olanzapine 10 mg was given intramuscularly if needed. However, on the third day after starting treatment, the patient began complaining of low-grade fever (37.8°C), nausea, and fatigue. Laboratory tests showed an increase in liver enzyme levels. However, several cases of severe liver toxicity due to clozapine use have been reported, and there are no specific guidelines for physicians to prevent or treat this condition. Close monitoring of liver function test (LFT) results is crucial in clozapine therapy, especially in considering the decision to stop treatment early if necessary.